Management Information Systems' Role and Effects on School Administration: A Review - Adhikari, Narayan Prasad; Budhathoki, Jhupa Kumari; Adhikari, Sharad (Perspectives on Higher Education, 2024)
This paper presents a comprehensive review of literature exploring the role and effects of Management Information Systems (MIS) in school administration. As educational institutions increasingly rely on technology to modernize and rationalize administrative processes, the integration of MIS has become vital. It assists management at different levels in making well-informed strategic decisions. The review highlights the multifaceted benefits of MIS, including enhanced decision-making, improved efficiency, and resource optimization within educational settings. Additionally, it examines the challenges and considerations associated with implementing MIS in schools, such as data security and privacy concerns, as well as the need for ongoing staff training and support. Through synthesizing existing research, this review underscores the key role of MIS in shaping modern school administration practices and offers insights for future research directions. Finally, the study offered that school administrators should keep in mind for effective future MIS policy and decision making.